2013
DOI: 10.1016/j.bbi.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Nerve-derived transmitters including peptides influence cutaneous immunology

Abstract: Clinical observations suggest that the nervous and immune systems are closely related. For example, inflammatory skin disorders; such as psoriasis, atopic dermatitis, rosacea and acne; are widely believed to be exacerbated by stress. A growing body of research now suggests that neuropeptides and neurotransmitters serve as a link between these two systems. Neuropeptides and neurotransmitters are released by nerves innervating the skin to influence important actors of the immune system, such as Langerhans cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 162 publications
(194 reference statements)
1
34
0
2
Order By: Relevance
“…In a nutshell, these studies mirror observations in other barrier tissues in that Substance P is pro-inflammatory, whereas CGRP has anti-inflammatory properties [87]. We refer the interested reader to the original literature and comprehensive reviews on this topic [87, 176, 181–184]. …”
Section: Role Of the Pns In Barrier Tissuessupporting
confidence: 56%
See 1 more Smart Citation
“…In a nutshell, these studies mirror observations in other barrier tissues in that Substance P is pro-inflammatory, whereas CGRP has anti-inflammatory properties [87]. We refer the interested reader to the original literature and comprehensive reviews on this topic [87, 176, 181–184]. …”
Section: Role Of the Pns In Barrier Tissuessupporting
confidence: 56%
“…In addition to PRR signaling, DCs and other myeloid leukocytes integrate signals from neuropeptide, which can influence cytokine profiles [87] (Figure 2). The pro-inflammatory activities of substance P were first mechanistically linked to enhanced production of IL-1, TNF-α, and IL-6 by monocytes [88].…”
Section: Role Of the Pns In The Development Deployment And Homeostamentioning
confidence: 99%
“…TRP and PGE2 can exhibit mutually enhanced function in the presence of one another, resulting in a lower threshold for TRP activation and increased pain sensation . Mast cell activation by neuropeptides can result in the release of histamine, which may influence vasodilation; tryptase, a chemotactic agent for fibroblasts; and MMP . Both fibroblasts and MMP have been implicated in fibrotic processes in rosacea skin and are surprisingly present in even the earliest stages of rosacea .…”
Section: Rosacea Pathophysiologymentioning
confidence: 99%
“…The authors suggested that this may be due to changes in the epithelial melanocyte system as a responsible mechanism [3]. Apart from α-MSH melanogenesis, pilosebase is involved in the inflammatory and immune response of the unit [13]. Increased α-MSH and MC-1R expression in sebaceous glands has been shown in patients with acne in the case of systemic or cutaneous stress.…”
Section: Discussionmentioning
confidence: 99%